the Representasi Feminisme Pada Film The Handmaiden (The Commercium, 2022)
Abstract The purpose of this paper is to discover, interpret, describe and analyze what the feminist movement looks like in breaking the patriarchal construction that took place in the film The Handmaiden. The research methods used in compiling this scientific article are interpretatif. The analytical technique used is qualitative using semiotics theory by John Fiske. This theory was chosen with the aim of being able to in detail represent the signs and symbols related to feminism in the film The Handmaiden. In addition, John Fiske's theory was chosen because it has a more detailed pattern to display or describe a symbol or sign, through the three levels, reality representation and believe system that he has as a benchmark unit of analysis where the research is headed. The results of this study show that the feminist movement in the fight against patriarchy by the two main female characters did occur, through the level of ideology how all the actions of figures who respect the role of men, but firmly fight when getting degrading treatment of women. In addition, the film also clearly depicts female focalization compared to men. Keyword : Film, Feminism, Semiotics, The Handmaiden